Managing ADHD in general practice. N of 1 trials can help! - Duggan, C; Mitchell, G; Nikles, C; Glasziou, P; Mar, D; Clavarino, A (2000)
OBJECTIVE: To pilot single patient trials designed to improve decision making about stimulant use for attention deficit hyperactivity disorder (ADHD) in general practice. METHOD: Patients previously stabilised on dexamphetamine were enrolled from a general practice. Each undertook a six week same patient randomised, double blind, placebo controlled crossover comparison of dexamphetamine with placebo for ADHD. Rating scales were completed weekly by self, parent and teacher. RESULTS: Three of the four patients were clear responders to dexamphetamine (including a noncompleter, as his results still demonstrated a clear response). The results were clinically useful in each case. Management was confirmed for three patients and changed for one (who ceased dexamphetamine). DISCUSSION: Prescribing stimulant medications only to children with diagnosed ADHD and who are found to respond, limits use of these worrisome drugs to those who will respond, and minimises their use in those who will not benefit.